2004
DOI: 10.1002/pits.20031
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of teacher appraisals of student behaviors

Abstract: The purpose of this study was to assess whether burnout and personality were linked to the perceived severity of 24 undesirable student behaviors among experienced and trainee teachers. Results indicated that teaching experience, student gender, and type of behavior were important determinants of their perceptions. Burnout had a significant effect on the severity ratings of antisocial and oppositional/defiant behaviors, suggesting that the more stressed teachers are, the less tolerant they become of such chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 23 publications
5
90
0
13
Order By: Relevance
“…Os resultados não confirmam a hipótese da pesquisa, uma vez que os professores do Ensino Especial apresentam índices mais elevados da dimensão de Ilusão pelo trabalho e menores nos perfis 1 e 2 de Burnout. Este resultado está em desacordo com a maior parte dos estudos internacionais (Kokkinos & Panayiotou, 2005;Lavian, 2012;Qutaiba, 2011;Roach, 2009) Pode-se entender este resultado a partir de questões culturais, pois crescem na literatura pesquisas atinentes à concepção de que estresse e Burnout podem ter diferentes configurações, a depender do contexto cultural, social e político da população em estudo (Etzion & Pines, 1986;Reichel & Neumann, 1993). Certos aspectos da manifestação de Burnout estão presentes em qualquer contexto sociocultural, embora, juntamente com as semelhanças, por vezes as manifestações assumam contornos específicos, determinados pelas particularidades do ambiente de trabalho, da organização e dos aspectos socioculturais mais amplos presentes nas diferentes sociedades (Moura, 1997;Vanheule, Rosseel, & Vlerick, 2007).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Os resultados não confirmam a hipótese da pesquisa, uma vez que os professores do Ensino Especial apresentam índices mais elevados da dimensão de Ilusão pelo trabalho e menores nos perfis 1 e 2 de Burnout. Este resultado está em desacordo com a maior parte dos estudos internacionais (Kokkinos & Panayiotou, 2005;Lavian, 2012;Qutaiba, 2011;Roach, 2009) Pode-se entender este resultado a partir de questões culturais, pois crescem na literatura pesquisas atinentes à concepção de que estresse e Burnout podem ter diferentes configurações, a depender do contexto cultural, social e político da população em estudo (Etzion & Pines, 1986;Reichel & Neumann, 1993). Certos aspectos da manifestação de Burnout estão presentes em qualquer contexto sociocultural, embora, juntamente com as semelhanças, por vezes as manifestações assumam contornos específicos, determinados pelas particularidades do ambiente de trabalho, da organização e dos aspectos socioculturais mais amplos presentes nas diferentes sociedades (Moura, 1997;Vanheule, Rosseel, & Vlerick, 2007).…”
Section: Discussionunclassified
“…Pesquisas desenvolvidas com o objetivo de comparar Burnout em professores do Ensino Especial e do ensino regular têm identificado maiores níveis de Burnout no Ensino Especial (Beck & Gargiulo, 1983;Kokkinos & Panayiotou, 2005;Lavian, 2012;Qutaiba, 2011;Roach, 2009). Em consonância com o exposto, o presente estudo teve como objetivo verificar se existem diferenças entres os índices das dimensões da SB e os dos perfis 1 e 2 em professores do Ensino Especial e do ensino regular.…”
Section: Introductionunclassified
“…In a large-scale qualitative study, Sutton, Mudrey-Camino and Knight (2009) showed that teachers were aware of the importance of emotion regulation but thought they sometimes lacked the skills to regulate negative emotions. Emotionally exhausted teachers were also more likely to describe student behaviour as disruptive (Kokkinos, Panayiotou, & Davazoglou, 2003). Furthermore, the more often teachers experienced negative affect in the classroom, the more negative students rated their instructional quality (Frenzel, Goetz, Stephens, & Jacob, 2009).…”
Section: Introductionmentioning
confidence: 89%
“…Lazarus and Folkman (1987) also emphasize circularity and explain that, although the cognitive-affective process of stress implies a temporal sequence, variables can be both antecedents and outcomes. For instance, burnout among teachers has been found to inflate perceptions of antisocial and oppositional behaviors (Kokkinos et al 2005).…”
Section: Transactional Model Of Stress and Copingmentioning
confidence: 99%